FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN PROTEIN POSITIF URINE PADA IBU HAMIL DI PUSKESMAS LAMPAHAN - Cut Ghina Usmaniar; Mawadhah Yusran; Zulfikar; Nurlaely HS (Akper Kesdam I/Bukit Barisan Padang, 2026)
ABSTRACTUrine protein examination is very important For done Because including in Wrong One method For know sign from preeclampsia. Mother pregnant need to do urine protein test for identify preeclampsia Good light and also weight that can leading on condition eclampsia. Besides that, examination This required For know function kidney during pregnancy. Study This done For know Factors influencing the incidence of positive urine protein in pregnant women at the Lampahan Health Center. Study This is study quantitative. Study This use design Cross Sectional. Population in study This is Mother pregnant who does examination at the health center Lampahan. Population in study This totaling 197 mothers pregnant from November 2024. Sample is part or representing all over the population that will examined. Determination amount sample with use formula slovin as many as 66 respondent. Based on results test Chi-square with level 95% confidence (α = 0.05 ) results calculation show p value (0.000) <α (0.05) means There is influence factor age Mother with urine protein occurrence. Result calculation show p value (0.001) <α (0.05) means There is influence factor age pregnancy with urine protein occurrence. Results calculation show p value (0.000) <α (0.05) means There is influence factor pressure blood with urine protein occurrence. Results calculation show p value (0.716) >α (0,05) means There is influence economic status factor with urinary protein occurrence. Study This It is expected that respondents Want to in a way independent capable recognize signs the beginning that can result in the occurrence of protein in the urine, in addition That can also provide additional information to pregnant women in increasing knowledge about midwifery care. Keywords : Age Mother, Age Pregnancy, Pressure Blood, Economy, Urine Protein